A review on voltage control methods using on-load tap changer transformers for networks with renewable energy sources. (September 2016) - Sarimuthu, Charles R.; Ramachandaramurthy, Vigna K.; Agileswari, K.R.; Mokhlis, Hazlie
Abstract: Voltage control is an important method for regulating the feeder voltages in a distribution network. Various voltage control methods are used by distribution network operators (DNOs) in order to maintain the network voltages to be within an acceptable voltage level. Traditionally, on-load tap changer (OLTC) and automatic voltage control (AVC) relays are often employed in regulating the network voltages. However, the traditional voltage control techniques are no longer suitable when renewable energy (RE) sources are connected to the network because of the possibility of bidirectional power flows. The presence of reverse power flow will affect the feeder voltage profiles and influence the voltage control scheme practiced in the distribution system. This paper presents an overview on the various OLTC voltage control schemes which are used to control the voltage in distribution networks containing RE sources.